Use of mufla oven calcination method in oil quantification of chia seeds - Silva, Tiago Roque Benetoli da; Ducheski, Rhaizza Lana Pereira; Silva, Gessica Daiane da; Ambrosano, Lucas; Gonçalves-Jr, Affonso Celso; Secco, Deonir; Alves, Charline Zaratin; Santos, Reginaldo Ferreira (Acta Iguazu, 2020)
Chia (Salvia hispanicaL.) is an annual herbaceous plant considered as natural omega-3 fatty acids source. To quantify this oil in seeds, a time-consuming method involving financial costs with chemical reagents is used. The objective of this work was verifying existence of correlation between the quantification of oil in chia seeds by means of the Soxhlet method with the ash mass of these seeds obtained by calcination in a muffle oven. For this, samples of chia seeds and the oil quantified by Soxhlet were collected. The same samples were calcined in ash. The simple correlation test was performed, obtaining linear regression. To method validation, a completely randomized design experiment was carried out. The treatments were to quantify the oil by the Soxhlet method and calcination in the muffle using the equation obtained. The objective was to verify the existence of correlation between the oil content of chia seeds, obtained by the Soxhlet method with ash content obtained after burning in the muffle and, therefore, the validation of this method of determination. There is a significant positive correlation between the oil content obtained by Soxhlet method and the ash mass of chia seed. By equation Y = -2.5319x + 16.518, it was noted that it is feasible to quantify the oil content